2016
DOI: 10.1002/14651858.cd009398.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids (PUFAs) for children with specific learning disorders

Abstract: Trusted evidence. Informed decisions. Better health. Cochrane Database of Systematic Reviews Both studies reported on ADHD-related behaviour. However, the format of available data did not allow us to readily combine them or to reach any conclusions. Included studies reported no other secondary outcomes. Conclusion Evidence is not su icient to support or refute the use of PUFAs in children with specific learning disorders. Polyunsaturated fatty acids (PUFAs) for children with specific learning disorders (Review) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Moreover, a search of the Cochrane library was also conducted to identify reviews regarding n -3 LCPUFA supplementation. The studies included in the Cochrane reviews were checked for inclusion in the current study [41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]. Lastly, for all included articles, the “cited by” option of Web of Science was checked (this option gives all articles that cite that specific article).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a search of the Cochrane library was also conducted to identify reviews regarding n -3 LCPUFA supplementation. The studies included in the Cochrane reviews were checked for inclusion in the current study [41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]. Lastly, for all included articles, the “cited by” option of Web of Science was checked (this option gives all articles that cite that specific article).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, EPA and DHA were found to be effective, in case methylphenidate was not [ 80 ]. Although a Cochrane meta-analysis of 2016 did not recommend EPA and DHA in the treatment of ADHD, other systematic reviews and meta-analyses reached more positive conclusions [ 81 , 82 , 83 ]. A very recent one concluded that, “a combination of eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA) ≥ 750 mg/d, and a higher dose of EPA (1200 mg/d) for those with inflammation or allergic diseases for duration of 16–24 weeks” would be beneficial in ADHD and that, “the current review also suggested that n-3 index and inflammation may be potential treatment response markers for youth, especially in ADHD and MDD, receiving n-3 PUFA.” [ 84 ].…”
Section: Children and Adolescentsmentioning
confidence: 99%
“…Results from these studies are summarized in recent reviews ( 56 , 116 ). In summary, these studies have investigated the use of atomoxetine (ATX), methylphenidate (MPH), and nutritional supplements such as polyunsaturated fatty acids ( 117 ) on outcomes of reading, ADHD symptoms, and executive functions in ADHD + RD groups. Reviews reporting on treatment studies found that outcome effect sizes range from small to medium [as low as 0.13 for ATX and as high as 0.60 for MPH ( 56 )], although effects on ADHD symptoms are larger and more consistent than for executive function or reading ( 56 , 116 ).…”
Section: Treatmentmentioning
confidence: 99%